MicroRNA-382 Promotes M2-Like Macrophage via the SIRP-α/STAT3 Signaling Pathway in Aristolochic Acid-Induced Renal Fibrosis - Wang, Xiaoyan; Jia, Ping; Ren, Ting; Zou, Zhouping; Xu, Sujuan; Zhang, Yunlu; Shi, Yiqin; Bao, Siyu; Li, Yingxiang; Fang, Yi; Ding, Xiaoqiang (Frontiers in Immunology, 2022)
Aristolochic acid nephropathy (AAN) is a type of drug-induced nephropathy and is correlated with a potentially progression of kidney fibrosis. However, whether miR-382 is implicated in macrophage activation in AA-induced kidney fibrosis remain elusive. Here, cell-sorting experiments defined a significant miR-382 enrichment in renal macrophage after AAN 14 days. Then, we found that treatment of AA induced a significant switch in phenotype of macrophage both in vivo and in vitro. Furthermore, miR-382 knockout mice and miR-382-/- bone marrow derived macrophage (BMDM) were subjected to AA induction. We found that miR-382 knockout notably suppressed M2-like macrophage activation both in vivo and in vitro as well as kidney interstitial fibrosis in vivo. Moreover, in cultured macrophage, upregulation of miR-382 promoted M2-related genes expression, accompanied by downregulation of signal regulatory protein α (SIRP-α) and activation of signal transducer and activator of transcription 3 (STAT3). The interaction between miR-382 and signal regulatory protein α (SIRP-α) was evaluated via dual luciferase assay. Knockdown of SIRP-α upregulated phosphorylated STAT3 at S727 and Y705. Pharmacological inhibition of (STAT3) was performed both in vivo and in vitro. Inhibition of STAT3 attenuated AA-induced kidney fibrosis, in parallel to lesser macrophage M2 polarization. Co-culture experiments further confirmed that overexpressed miR-382 in macrophage promoted injuries of tubular cells. Taken together, our data suggest that miR-382 is a critical mediator in M2-like macrophage polarization and can be a promising therapeutic target for kidney fibrosis.